Wireless air purification with IOT / Muhammad Hazim Iqbal Paiman - Paiman, Muhammad Hazim Iqbal (2024)
Nowadays, air pollution often occurs because of chemicals in the air that can have a bad effect on human lungs. in addition, there are also substances dispersed in the air which are small molecules that can trigger shortness of breath and asthma. as a result, there are many cases such as fainting and even worse can cost lives because the air quality is so bad. In this modern age, all information can be accessed at the end with IoT. This includes improving ventilation and measuring air quality using IoT. In this scenario, IoT can also be used widely such as to control ventilation to be clean, measure temperature and humidity and check the quality of the air around us. Therefore, with good ventilation and being able to measure air quality, temperature and humidity, all diseases that cause breathing problems can be avoided. This study proposes Smart Air Purifier. The aim of this study is divided into 3 parts. The first part is the hardware development that consists of two sensors which are air quality sensors, temperature, and humidity sensor as input, to measure air quality, temperature and humidity while dc motor, fan, air filter and motor driver as output to filter polluted materials in the air. Then, LCD display to display the output of the sensor reading, and ESP8266 as the main controller. The second part is to display the information of the output and allows users to control fan rotation speed using mobile phone. Here, this system can help to provide cleaner ventilation at the same time can reduce a person from getting sick